Reconstruction of post electrical burns scalp defect - Kotera, Sai Suraj; Narayan, Naveen; M. S., Mahesh; Dhanraj, Prema (International Journal of Research in Medical Sciences, 2017)
Pertinent approach for scalp reconstruction often poses a challenge to plastic surgeons due to numerous reasons like inelastic nature of scalp, hairy nature of scalp and others. Traditional surgical treatment of deep burns of the scalp and skull involved excision of necrotic bone and soft tissues with trephanation of the bone to permit granulation tissue formation followed by skin grafting. However, this approach prolongs wound time and adds additional trauma. Even after initial healing it may necessitate secondary soft tissue and bone reconstruction. Treatment of scalp defect after electrical burn is managed according to the amount of damage. Scalp burn injury with osteomyelitis of the calvarium is seldom mentioned in literature. In the present case, the defect was long standing with skull exposure and hence routine management of scalp defect had to be differed. The calvarial bone was replaced with sequestrum. Complete excision of the sequestrum was done with intact dura. Ensuing defect was covered with local transposition flap. The donor area was covered with split thickness skin graft.